Cannabis Significantly Reduces the Use of Prescription Opioids and Improves Quality of Life in Authorized Patients: Results of a Large Prospective Study. Issue 3 (27th December 2020) - Lucas, Philippe; Boyd, Susan; Milloy, M.-J.; Walsh, Zach
Abstract: Objectives: This article presents findings from a large prospective examination of Canadian medical cannabis patients, with a focus on the impacts of cannabis on prescription opioid use and quality of life over a 6-month period. Methods: The Tilray Observational Patient Study took place at 21 medical clinics throughout Canada. This analysis includes 1, 145 patients who had at least one postbaseline visit, with follow-up at 1, 3, and 6 months. Instruments included a comprehensive cannabis use inventory, the World Health Organization Quality of Life Short Form (WHOQOL-BREF), and a detailed prescription drug questionnaire. Results: Participants were 57.6% female, with a median age of 52 years. Baseline opioid use was reported by 28% of participants, dropping to 11% at 6 months. Daily opioid use went from 152 mg morphine milligram equivalent (MME) at baseline to 32.2 mg MME at 6 months, a 78% reduction in mean opioid dosage. Similar reductions were also seen in the other four primary prescription drug classes identified by participants, and statistically significant improvements were reported in all four domains of the WHOQOL-BREF. Conclusions: This study provides an individual-level perspective of cannabis substitution for opioids and other prescription drugs, as well as associated improvement in quality of life over 6 months. The high rate of cannabis use for chronic pain and the subsequent reductions in opioid use suggest that cannabis may play a harm reduction role in the opioid overdose crisis, potentially improving the quality of life of patients and overall public health.